(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
The purpose of this paper is to show the role of the common past in the emergence and development of some smaller European nations. Shared past in the Balkans is seen solely through the prism of nationalism. When someone talks about a shared history, he does it in order to show that the others in that history have no past. There are several examples of shared history worldwide and it is normally not a problem, except in our region. Also, the role of a person in the past of two or more nations is very common and it should not be a ground for misunderstanding and conflict. Fluidity of ethnic identity is not associated only with the Balkans; it is also present in some other European countries. Such is the case, for example, with Lithuania. In addition, when it comes to the role of reformers and intellectuals who had different ethnic backgrounds in the emergence and development of some modern European nations, we may observe that there are such examples, for instance, in Finland and Estonia. Unlike the Balkans, shared histories, common personalities and intellectuals who had different ethnic backgrounds in terms of nations where they contributed greatly, in some European countries it does not mean denial of the right to self-determination and existence.